Perinatal outcomes of vacuum assisted versus cesarean deliveries for prolonged second stage of delivery at term*. (18th April 2017) - Shmueli, Anat; Salman, Lina; Ashwal, Eran; Hiersch, Liran; Gabbay-Benziv, Rinat; Yogev, Yariv; Aviram, Amir
Abstract: Introduction : To compare perinatal outcomes of interventions for prolonged second stage of labor. Materials and methods : Retrospective cohort study, in a single, university-affiliate, medical center (2007–2014). Eligibility: singleton gestations at term, diagnosed with prolonged second stage of labor and head station of S + 1 and lower. We compared perinatal outcomes of cesarean deliveries (CD) with vacuum assisted deliveries (VAD). Results : Of 62 102 deliveries, 3449 (5.6%) were eligible: 356 (10.3%) underwent CD and 3093 (89.7%) underwent VAD. The rate of five-minute Apgar scores <7 was higher in the CD group as well as rates of NICU admission, neonatal asphyxia and composite neonatal adverse outcome. After adjusting for different confounders, CD was associated with adverse neonatal composite outcome (aOR 1.57, 95% CI 1.21–2.05, p = 0.001) and VAD with cephalhematoma (aOR 4.06, 95% CI 2.64–6.25, p < 0.001). No other differences were found between the groups with regards to other traumatic outcomes. Conclusion : Our data suggests that in deliveries complicated by prolonged second stage, CD yield poorer neonatal outcome than VAD, with no apparent major difference in traumatic composite outcome.